Joyful Encounters: Learning to Play Well with Machines. Issue 1 (19th January 2021) - Sandry, Eleanor; Peaty, Gwyneth
Human interactions with machines, including computers, consoles, smart devices and robots, are becoming more and more a part of everyday life. However, human–machine relations are often regarded as problematic for people, their interpersonal communication and human society more broadly. This paper provides an analysis of the characteristics that constitute 'play' in relation to video games and interactions with robots, arguing it is possible to position time spent on play with machines as valuable in itself, without requiring the outcomes more traditionally regarded as productive. Much of what is valuable in play can be seen to develop from embodied processes of communication within which humans and machines encounter and respond to one other. These encounters are often shaped by stories about the capabilities of machines and humans, while the interactions themselves go on to provoke new narratives. Although human–machine interaction can be theorized as 'cyborg' or 'hybrid', this paper argues that adopting the idea of the 'assemblage' is a better way recognize the flexibility of bringing disparate humans and machines together, whether in relation to playing a game or playing music. In rethinking the value of play, this paper emphasizes how people's time spent interacting, whether with video games or robots, provides opportunities for them to learn more about themselves and others.